Is Happiness Infectious?. (8th January 2016) - Knight, John; Gunatilaka, Ramani
Abstract: The paper uses an appropriate survey from rural China to answer the question: is happiness infectious, i.e. does the happiness of an individual depend positively on the happiness of his or her reference group? The evidence is consistent with this hypothesis, but the challenge is to solve the 'reflection problem', i.e. is the apparent effect of neighbours' happiness on own happiness a causal one or merely a reflection? A 'quasi‐panel' approach is adopted, treating villages as groups and individuals as multiple observations within each group, and using an error components 2SLS estimator. The results suggest that the relationship might be largely causal. The normative and policy implications are briefly considered.